Planning Concept on Islamic Education Management - Imron Muttaqin (Yayasan Letiges Konsultan Sosial, 2023)
This study aims to find planning concepts of Islamic Education management; based on this purpose, this research uses library research because it can export and find core concepts from various sources, especially from Qur'anic verses. Planning is determining policies and programs by utilizing all resources to achieve goals based on Islamic values. Planning must be intended for worship in the hope of being given ease and success by Allah SWT, with the full awareness that everything comes from Allah (minallah), with the power of Allah (billah) and will return to Allah SWT (ilallah).